A study on shelter airport selection during large-scale volcanic disasters using CARATS open dataset. (August 2021) - Arreeras, Saharat; Arimura, Mikiharu
Highlights: The proposed airport selection model is based on Mt.Hakone and Japan's air traffic. The model is constructed on ash coverage area, aircraft, and airport assumptions. The genetic algorithm (GA) is applied to find the approximate solution. The greedy randomized adaptive search procedure (GRASP) is used as a benchmark. Abstract: Air transport supports economic growth and prosperity through the movement of passengers and goods. As it grows more extensive and more complex, the more vulnerable its operations to unexpected natural disasters (e.g., typhoon and volcanic eruption) will become. In Japan, many active volcanos are affecting its airspace and considered a threat to the national air transportation and critical aviation equipment such as aircraft. The study focuses on solving the evacuation of the affected aircraft during the volcanic eruption by proposed the shelter airport selection model using the historical data of volcanic eruption, aircraft movement, and airports data in Japan. The model was applied to the genetic algorithm (GA), the metaheuristic algorithm to provide the approximate solution of the suitable shelter airport with minimum flight time and no exceeded shelter airports' capacities for the aircraft evacuation.